PENGARUH KINERJA PUSTAKAWAN TERHADAP PEMUSTAKA DI UPT PERPUSTAKAAN UNIVERSTAS TANJUNGPURA - Ningsih, Ayu Irma; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study discusses the performance of a librarian in the of Tanjungpura University. The purpose of this study is to find out how big is the role a librarians in serving the librarian in Tanjungpura University. An institution library is a library located in the area of Higher Education with the aim to provide information to researches who need it. Thearfore, in a library must have manager who understands in the field if library science. The manager is called a Librarian. The Librarian is an expert in the field of library science, working as a collection organizerÂ  and also as a manager of information. A librarian performance should also be noted because to support a beeter library. A good impression of a libraryship is how a librarian serves visitors. a good library ship will always provide the best service for visitors. Â Key Words: Institut Library, Librarian, Performance